Effects of Fe additive on diamond crystallization from carbonyl nickel powders-C system under HPHT condition *Project supported by the National Natural Science Foundation of China (Grant No. 51172089), the Natural Science Foundation of Guizhou Provincial Education Department, China (Grant No. KY [2013]183), and the Research Fund for the Doctoral Program of Tongren University, China (Grant Nos. DS1302 and trxyS1415). (August 2015) - Li, Yong; Jia, Xiao-Peng; Feng, Yun-Guang; Fang, Chao; Fan, Li-Juan; Li, Ya-Dong; Zeng, Xiang; Ma, Hong-An
Abstract In this paper, diamond crystallization from carbonyl nickel powders-C and carbonyl nickel powders+Fe–C systems are investigated in detail at a pressure of 6.0 GPa and temperatures ranging from 1410 °C–to 1435 °C by temperature gradient growth. The effects of Fe additive on the crystal morphology are discussed in the diamond crystallization process. Furthermore, Fourier infrared measurement results indicate that the spectrum of the diamond obtained from Ni + Fe–C system after annealing treatment is nearly consistent with that of natural diamond crystal. We believe that this study is of benefit to a further understanding of the growth mechanism of natural diamond.